The pandemic : perspectives on Asia - Chaturvedi, Vinayak (Asia shorts ;, 2021)
"This collection of essays provides analyses of the COVID-19 pandemic in Asia. It covers the first phase of the pandemic that will help future scholars to contextualize the history of the present. It includes interpretations by leading scholars in anthropology, food studies, history, media studies, political science, and visual studies, who examine the political, social, economic, and cultural impact of COVID-19 in China, India, Korea, Japan, Taiwan, and beyond"--